Development and validation of an ultraviolet-visible spectrophotometric method for quantifying oxytetracycline for veterinary use - Kaluka Tshibamba, Jacques Mbuyi; Kakumba, Jocelyn Mankulu; Mabaya, Timothy Mavanga; Djang’ieng’a, Roland Marini; Kindenge, Jérémie Mbinze (Frontiers in Analytical Science, 2023)
Livestock breeding plays a key role in sub-Saharan Africa because it is an important source of highly valued protein in the human diet, and because it is an essential driver for socio-economic development. It represents a form of investment and is also important from a socio-cultural point of view (ceremonies, social position, etc.). Livestock is an important source of income, livelihood, nutrition, and food security. However, livestock breeding faces, among other things, major sanitary constraints. Furthermore, the circulation of non-compliant antibiotics on the market constitutes a major threat to animal health, public health, and the environment. This research aims to develop and validate a UV-vis method for quantifying pharmaceutical oxytetracycline. The method developed was validated following the total error strategy as a decision tool in the accuracy profile. After its completion, the method demonstrated good absolute and relative bias and was within a tolerable interval of [−2%, +2%]. The method was also repeatable with intermediate precision, with respectively lower values than 2% and 4%. We also assessed the recovery and accuracy of the method as fitting with the specification limits. After its validation, the method was quantified in 47 oxytetracycline injectable samples, where we obtained 28 samples complying with specifications and 19 that did not. That led us to conclude that the developed method was validated and appropriate for quantification in terms of the routine quality control of oxytetracycline injection. The method needs to be reviewed and revalidated accordingly for other pharmaceutical presentations.